The Genetics of Human Schistosomiasis Infection Intensity and Liver Disease: A Review - Mewamba, Estelle M.; Nyangiri, Oscar A.; Noyes, Harry A.; Egesa, Moses; Matovu, Enock; Simo, Gustave (Frontiers in Immunology, 2021)
Background Schistosomiasis remains the fourth most prevalent parasitic disease affecting over 200 million people worldwide. Control efforts have focused on the disruption of the life cycle targeting the parasite, vector and human host. Parasite burdens are highly skewed, and the majority of eggs are shed into the environment by a minority of the infected population. Most morbidity results from hepatic fibrosis leading to portal hypertension and is not well correlated with worm burden. Genetics as well as environmental factors may play a role in these skewed distributions and understanding the genetic risk factors for intensity of infection and morbidity may help improve control measures. In this review, we focus on how genetic factors may influence parasite load, hepatic fibrosis and portal hypertension. Methods The schistosomiasis associated phenotypes reviewed were: egg/worm burden and pathology defined as hepatic fibrosis and portal hypertension. We also undertook automated searches of PubMed to find papers associated with schistosomiasis and each of the genes in the QTL regions. Results We found 28 studies on the genetics of human infection and 20 studies on the genetics of pathology in humans. S. mansoni and S. haematobium infection intensity have been showed to be controlled by a major quantitative trait locus SM1, on chromosome 5q31-q33 containing several genes involved in the Th2 immune response, and three other loci of smaller effect on chromosomes 1, 6 and 7. The most common pathology associated with schistosomiasis is hepatic and portal vein fibroses and the SM2 quantitative trait locus on chromosome 6 has been linked to intensity of fibrosis. Although there has been an emphasis on Th2 cytokines in candidate gene studies, we found that four of the five QTL regions contain Th17 pathway genes that have been included in relation schistosomiasis studies: IL17B and IL12B in SM1, IL17A and IL17F in 6p21-q2, IL6R in 1p21-q23 and IL22RA2 in SM2. The Th17 pathway is known to be involved in response to schistosome infection and hepatic fibrosis but variants in this pathway have not been tested for any effect on the regulation of these phenotypes. These should be priorities for future studies.